an exploratory study of motivations for Chinese Post-80s consumers to purchase luxury products - Fu, Xiaofeng (2010)
ABSTRACT This dissertation mainly aims at making a deep exploration of China Post-80s consumers’ perceptions of luxury products and why China Post-80s consumers purchase them. The existing literature on luxury is reviewed and using the framework, developed by Tynan, McKechnie and Chhuon (2009), as the basis for analysis.8 interviewees, aging in the range between 21 and 27 from Hangzhou China were interviewed for understanding the research questions in an interpretive approach. The study indicates the different perceptions of understanding the word of ‘luxury’ between Chinese and Westeners, where Chinese are likely to associate this word with negative meaning which is “wasteful and lavish”. Moreover, compared to older generations, China Post-80s consumers appeared to understand luxury products based on utilitarian value, relational value and cost/sacrifice value which is in much wider perspective.